Child Day Care Center Use and Mental Stress of Working Mothers - Himika, Tasnuva Nawrin; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2022)
Background: Some of the working mothers use child day care center (CDCC) for their children to reduce their mental stress. This study was designed to assess the association between mental stress of working mothers and child day care center use. Methods: This comparative cross sectional study was conducted among 106 working mothers of whom 53 were CDCC users and 53 were non-users from January to December, 2019. Data were collected by face to face interview by a semi-structured questionnaire. Mental stress was estimated by Perceived Stress Scale (PSS). Data were analyzed by the Statistical Package for Social Sciences. Quality control checks for data were done. All ethical issues were maintained strictly in different stages of the study and informed written consent was taken from each individual. Results: Mean (±SD) age was 32.92(± 2.901) and 33.55(± 3.160) years in CDCC users and non-users respectively. Average monthly family income was Tk.191698.11 in CDCC users and Tk. 209433.96 in non-users. Majority (67.9%) of the CDCC users lived in nuclear family while 67.9% of the CDCC non-users lived in joint family. Mothers had significantly higher (85.5%) stress who had maid servant in comparison to mothers who had not and mothers had higher (75.0%) stress who suffered from illness compared to mothers who did not suffer and it was significant (p<0.05). Both low (61.5%) and moderate (59.4%) stress were significantly higher among CDCC users while high stress (83.3%) was significantly higher among CDCC non-users. Chance of having low stress was high (OR=8.0) in mothers who were CDCC users than mothers who were CDCC non-users. Conclusion: CDCC non-users had high level of mental stress than the CDCC users. CDCC should be established with every organization to reduce the mental stress of working mothers. JOPSOM 2021; 40(1): 59-65